REPORT OF THE ANNUAL CONVENTION. - Walgenbach, Paul H. (The Accounting Review, 1964)
The 1963 annual meeting of the American Accounting Association was held on August 26, 27 and 28 at Stanford University, Stanford, California. Facilities of the University, coupled with the excellent arrangements made the meeting very successful and enjoyable. The program for the Plenary session on Tuesday morning presented discussion on Standards of Accounting Education. At the Wednesday afternoon Plenary session speakers presented topics related to Responsibility Reporting to Management. In addition to the Plenary sessions, a wide variety of topics were discussed, some of which were Undergraduate Accounting Standards, Capital Investment Planning, New Approaches to Accounting Theory, Graduate and Professional Programs, Accounting for the Investment Credit, Management Services and the Certified Public .Accountants Examination. At the Wednesday luncheon and business meeting, President Walter G. Kell reviewed the work of the Committees and other Association activities. Membership Chairman David W. Phipps reported on membership changes and activities. Secretary-Treasurer Paul H. Walgenbach, presented an interim financial report.